Evaluation of the extent of ketamine-induced uropathy: the role of CT urography - Huang, Li-Kuo (BMJ Publishing Group, 2014)
BACKGROUND: With growing ketamine abuse, ketamine-induced uropathy (KIU) has become more prevalent in recent years. This research evaluates the presence, distribution and extent of KIU in the upper and lower urinary tracts by retrospectively reviewing CT urography (CTU) images. METHODS: Patients diagnosed with KIU who underwent CT scanning from 1 January 2006 to 31 December 2011 were recruited. The CT protocols included three-phase CTU in six patients, split-bolus CTU in 17, two-phase CT in one and unenhanced CT in three. The CT images were retrospectively reviewed by two radiologists. RESULTS: A total of 27 patients participated in this study. The common CT findings included diffuse bladder wall thickening (88.9%), small bladder volume (66.7%) and perivesical inflammation (44.4%). Twelve patients (44.4%) were diagnosed with hydronephrosis, including three patients with unilateral hydronephrosis and nine with bilateral hydronephrosis. Of these patients, nine had ureteral wall thickening (33.3%) and two (7.4%) had ureterovesical junction involvement (ie, they had hydronephrosis but no ureteral wall thickening). One patient had a ureteral obstruction because of a ureter stone. The correlation between upper urinary tract involvement and grading of the interstitial cystitis was statistically non-significant (p=0.33). Four patients (14.8%) had a vesicovaginal fistula which could be detected in the excretory phase only. CONCLUSIONS: Upper urinary tract involvement is common in patients with KIU. CTU might aid evaluation of the extent of KIU and prompt adequate management.